Warfarin use increases bleeding risk in hemodialysis patients with atrial fibrillation: A meta‐analysis of cohort studies. Issue 6 (29th January 2019) - Hussain, Salman; Siddiqui, Ali Nasir; Baxi, Harveen; Habib, Anwar; Hussain, Md Sarfaraj; Najmi, Abul Kalam
Abstract: Background and Aim: Atrial fibrillation is one of the most common comorbid conditions in hemodialysis patients, and warfarin is widely prescribed anticoagulant to prevent thromboembolic complications in such patients. In the last decade, several epidemiological studies pointed out the risk of bleeding with the use of warfarin. So, this meta‐analysis is aimed to assess the bleeding risk associated with the use of warfarin. Methods: This meta‐analysis was conducted in accordance with the Preferred Reporting Items for Systematic Review and Meta‐analysis guidelines. PubMed, Embase, Scopus, and Cochrane central databases were searched from inception to June 10, 2018. The primary outcome was to quantify the bleeding risk associated with warfarin use. The secondary outcome was to assess the bleeding risk based on different subgroups. Review Manager (RevMan) version 5.3 was used for performing statistical analysis. Results: A total of 15 studies, constituting a pooled sample of 53 581 patients (37.14% female), were included. Of these, 17 469 were warfarin users. We found that warfarin use had a significant association with the bleeding risk. The pooled relative risk (RR) of bleeding was estimated to be 1.35 (95% CI: 1.18–1.53, P  = < 0.00001), and the pooled RR of major bleeding (five studies) was estimated to be 1.32 (95% CI: 1.07–1.63, P  = 0.009). Subgroup analysis revealed a significant association of warfarin use with the intracranial hemorrhage/hemorrhagic stroke (nine studies) (pooled RR: 1.43 [95% CI: 1.20–1.71, P  = < 0.0001]). Conclusions: The results indicate that warfarin use increases the risk of bleeding in hemodialysis patients with atrial fibrillation.